In vitro virulence of yeasts isolated from the cervicovaginal region of bitches - Antonio, Denise S. N.; Abreu, Daniel P. B. de; Bonci, Mario M.; Makita, Mario Tatsuo; de Campos, Sergio Gaspar; Baroni, Francisco de Assis (Brazilian Journal of Veterinary Medicine, 2018)
The present study verified the species of yeast present in cervicovaginal mucosa of bitches and the in vitro production of virulence factors. A total of 40 female dogs were divided into not neutered and pregnant groups and samples were collected implementing cervical-vaginal lavage with sterile saline. Isolation was performed in Brain and Heart Infusion Agar, followed by morphological, biochemical and physiological evaluations for phenotypical identification of yeasts, and determination of phospholipase and protease production using specific mediums. Fungal growth was obtained in 33 animals (82.5%), totalizing 60 isolates. Candida spp was the most prevalent genus, with 21 isolates (35.0%), followed by 19 (31.66%) Malassezia spp, 13 (21.66%) Rhodotorula spp, and 7 (11.66%) Trichosporon spp. For the evaluation of protease production, 36.66% were negative, while 33.33% positive and 30.0% strong positive. For phospholipase production 45.0% were negative, 16.66% positive, and 28.33% strong positive. Most of the isolates showed some degree of virulence, considering the production of these two enzymes, and were previously described as infectious agents of the reproductive tract. A better understanding of the genital tract microbiota could potentially clarify some reproductive disorders in small animal practice.